The Allegorical House of Temperance: on the Semantics of Space in Spenser’s Faerie Queene - Elena V. Haltrin-Khalturina (Studia Litterarum)
The article focuses on the semantics of space within Spenser’s chivalric allegory The Faerie Queene (1590/1596). Special attention is paid to the spatial model of allegorical castle from the second book of the poem. Spenser’s artistic manner is considered; in particular, his partaking of the mannerist style. There is offered an analysis of one of the most puzzling passages of the poem, the House of Temperance. The castle’s keep (the residence of the fair soul called Alma) is shaped as a healthy human body, housing several allegorical rooms. The keep of this allegorical castle was extensively discussed in criticism, as it seems, to the detriment of its fortifications and surroundings, without which the whole allegorical picture remains rather incomplete. This article considers the castle of Temperance in its wholeness, including the allegorical topography of its landscape. The keep/body is surrounded by a system of bulwarks, forming a structure similar to a pentangle: each bastion stands for one of the five senses. On the one side of the castle, there are wild woods where monsters (sins and seductions) live; on the other side, there is a lake holding the waters of baptism. The eclectic castle of Temperance is studied against the cultural and scholarly background of Spenser’s epoch. This article is a revised version of a paper presented at the 27 th Shakespeare Readings (Moscow, 2018).